New and rare for Ukraine lichens from Nature Reserve “Yelanetsky Step” (CHORNOMORSKI BOTANICAL JOURNAL, 2009)
Distribution and ecology of two new for Ukraine lichen species (Toninia physaroides(Opis) Zahlbr.and Caloplacamuscorum(A.Massal.) M.Choisy& Werner) and 14 rare speciesfrom nature reserve“Yelanetsky Step” are elucidated in the article.
Keywords: lichens, limestone, localities, steppe zone of Ukraine.